2020
DOI: 10.1055/s-0040-1715773
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Comparison of Efficiencies of Bacteriophages to Reduce Planktonic and Biofilm-Associated Staphylococcus aureus

Abstract: Introduction In the present era, wherein occurrence of antimicrobial resistance compounded with biofilms in disease conditions has rendered present antibiotic therapy ineffective, the need for alternative strategies to treat bacterial infections has brought bacteriophages to the forefront. The antimicrobial activity of phages is often determined by a viable cell reduction assay which focuses only on planktonic forms. The physiology of an organism in biofilm differs from those that are planktonic; hence, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Novel phage F 15 produces a polysaccharide depolymerase that hydrolyzes the EPS of a single species of single-species Pseudomonas putida and inhibits biofilm formation (Cornelissen et al, 2011). Rai et al (2020) used CV staining to determine the biofilm content. They found that phage PD1 and PE2 could effectively prevent the formation of S. aureus biofilms, while PD1, PE1, and P3 could disperse mature biofilms.…”
Section: Bacteriophagementioning
confidence: 99%
See 1 more Smart Citation
“…Novel phage F 15 produces a polysaccharide depolymerase that hydrolyzes the EPS of a single species of single-species Pseudomonas putida and inhibits biofilm formation (Cornelissen et al, 2011). Rai et al (2020) used CV staining to determine the biofilm content. They found that phage PD1 and PE2 could effectively prevent the formation of S. aureus biofilms, while PD1, PE1, and P3 could disperse mature biofilms.…”
Section: Bacteriophagementioning
confidence: 99%
“…Novel phage Φ 15 produces a polysaccharide depolymerase that hydrolyzes the EPS of a single species of single-species Pseudomonas putida and inhibits biofilm formation ( Cornelissen et al., 2011 ). Rai et al. (2020) used CV staining to determine the biofilm content.…”
Section: Strategies Against Bacterial Biofilm Removalmentioning
confidence: 99%
“…However, reports of phages have shown promising results in vitro but failed to deliver the same in vivo. This difference is because phage efficacy is often tested only on planktonic cells, but in vivo, organisms form biofilms that provide better survival [ 13 , 14 ]. The ability of P. aeruginosa to form biofilms correlates with its ability to impair the healing of diabetic wounds [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three 1 2 3 have some diagnostic care component and the subject of the other three is the laboratory diagnosis of COVID-19. 4 5 6 Since JHAS-NU began in 2016, there have been 2 publications on biofilms, 7 8 3 publications on the microbiome, 9 10 11 2 publications on nanotechnology, 12 13 and 1 publication on probiotics. 14…”
mentioning
confidence: 99%